Withaferin A Inhibits Neutrophil Adhesion, Migration, and Respiratory Burst and Promotes Timely Neutrophil Apoptosis - Bayless, Rosemary L.; Sheats, M. Katie; Jones, Samuel L. (Frontiers in Veterinary Science, 2022)
Neutrophils play a major role in many equine conditions, including equine asthma, laminitis, and intestinal ischemia and reperfusion injury, and therefore represent an attractive target for innovative therapeutic approaches. Novel strategies for reducing neutrophilic inflammation include modulation of neutrophil functions and lifespan. Withaferin A (WFA) is a phytochemical with well-established in vitro and in vivo anti-inflammatory properties, but its direct effects on neutrophils are largely unknown. We hypothesized that WFA would inhibit adhesion, migration, and respiratory burst by equine neutrophils and promote timely apoptosis of primed equine neutrophils. Consistent with this hypothesis, our data show that WFA causes a significant, concentration-dependent inhibition of equine neutrophil adhesion, migration, and respiratory burst in response to diverse stimuli. Further, WFA treatment increased apoptosis of equine neutrophils exposed to GM-CSF for 24 hours. This pro-apoptotic effect of WFA was not observed in unprimed neutrophils, nor at the 2-hour time point relevant to our functional neutrophil experiments. Our data demonstrate that WFA may reduce neutrophil-mediated inflammation through multiple mechanisms, including suppression of inflammatory responses and promotion of apoptosis. Additional research is needed to elucidate the molecular mechanisms for these effects and evaluate the potential clinical use of WFA in veterinary and human patients.